ABU HAMID ABOUT SCIENCE AND ENLIGHTENMENT IN GHAZALI’S RELIGIOUS VIEWS - Eshanova Gulchehraxon Numonovna (International Engineering Journal For Research & Development, 2021)
The great thinker of Islam, Abu Hamid al-Ghazali, analyzed the greatness of knowledge and enlightenment in Islam on the basis of the Qur'an and the hadiths. Islam emphasizes not only the greatness of science, but also the role of enlightened scholars in society.